2018
DOI: 10.1038/s41419-018-0272-z
|View full text |Cite
|
Sign up to set email alerts
|

The type 2 diabetes-associated HMG20A gene is mandatory for islet beta cell functional maturity

Abstract: HMG20A (also known as iBRAF) is a chromatin factor involved in neuronal differentiation and maturation. Recently small nucleotide polymorphisms (SNPs) in the HMG20A gene have been linked to type 2 diabetes mellitus (T2DM) yet neither expression nor function of this T2DM candidate gene in islets is known. Herein we demonstrate that HMG20A is expressed in both human and mouse islets and that levels are decreased in islets of T2DM donors as compared to islets from non-diabetic donors. In vitro studies in mouse an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
56
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(62 citation statements)
references
References 48 publications
(57 reference statements)
6
56
0
Order By: Relevance
“…Among the 34 T2D susceptibility loci listed by Bonnefond and Froguel (11) that affect insulin secretion or islet function, we find seven that contact INS, indicating that there is enrichment of those loci in the contact region (χ 2 test, P = 0.003). A recent report showed that the expression levels of one of the loci, the HMG20A gene, are decreased in islets from T2D donors compared with islets from nondiabetic donors (29). The enrichment of T1D susceptibility loci is more significant, as the HLA loci resides inside the 4C contact regions.…”
Section: Resultsmentioning
confidence: 99%
“…Among the 34 T2D susceptibility loci listed by Bonnefond and Froguel (11) that affect insulin secretion or islet function, we find seven that contact INS, indicating that there is enrichment of those loci in the contact region (χ 2 test, P = 0.003). A recent report showed that the expression levels of one of the loci, the HMG20A gene, are decreased in islets from T2D donors compared with islets from nondiabetic donors (29). The enrichment of T1D susceptibility loci is more significant, as the HLA loci resides inside the 4C contact regions.…”
Section: Resultsmentioning
confidence: 99%
“…The Proline-Serine-Threonine Phosphatase Interacting Protein 1 (PSTPIP1) gene is a tyrosine phosphatase that inhibits T-cell activation upon T-cell receptor (TCR) and CD28 engagement, regardless of CD2 co-stimulation [37]. The HMG20A gene had higher expression in islets than in muscle and adipose tissue [38], and a transient increase in expression levels was observed upon glucose stimulation [38]. HMG20A has been reported to be down-regulated in T2D and T1D islets, and knockdown of HMG20A decreased expression of NEUROD, INS and GK with an accompanying impairment in GSIS [38].…”
Section: Discussionmentioning
confidence: 99%
“…The HMG20A gene had higher expression in islets than in muscle and adipose tissue [38], and a transient increase in expression levels was observed upon glucose stimulation [38]. HMG20A has been reported to be down-regulated in T2D and T1D islets, and knockdown of HMG20A decreased expression of NEUROD, INS and GK with an accompanying impairment in GSIS [38]. Therefore, this SNP could through its eQTL effect on HMG20A expression in islets be a plausible candidate gene for GDM.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes is caused by a progressive loss of β‐cell insulin secretion frequently against a background of insulin resistance, or autoimmune β‐cell destruction, usually leading to absolute insulin deficiency . Among the 50 SNPs included in this study, most loci exerted their primary effects on disease risk through deficient insulin secretion, some loci were related to insulin resistance or insulin sensibility, and some loci may be the adapter or receptor that can indirectly affect insulin sensitivity or increase diabetes susceptibility …”
Section: Discussionmentioning
confidence: 99%
“…22,23 Among the 50 SNPs included in this study, most loci exerted their primary effects on disease risk through deficient insulin secretion, some loci were related to insulin resistance or insulin sensibility, and some loci may be the adapter or receptor that can indirectly affect insulin sensitivity or increase diabetes susceptibility. 8,10,28,32,[36][37][38][39][40][41][42][43][44] Among the susceptibility loci examined herein, we confirmed significant evidence for an association with diabetes risk for 10 loci in the Chinese population in the following genes: cyclindependentkinase 5 regulatory subunit associated protein 1 (CDKAL1) (rs10946398), adaptorrelated protein complex 3 subunit sigma 2 (AP3S2) (rs2028299), SREBF chaperone (SCAP) (rs4858889), RAS guanyl releasing protein 1 (RASGRP1) (rs7403531), Gprotein-coupled receptor kinase 5 (GRK5) (rs10886471), diacylglycerol kinase beta/transmembrane protein 195 (DGKB/TMEM195) (rs2191349), zinc finger AN1-type containing 3 (ZFAND3) (rs9470794), kelchdomain containing 5 (KLHDC5) (rs10842994), melatonin receptor 1B (MTNR1B) (rs10830963), and ankyrin1 (ANK1) (rs516946). Previous studies have identified an association between diabetes risk and SNPs for CDKAL1 in European Americans, African Americans, UK samples, Indians, Korean, and Chinese, 33,[45][46][47][48][49] making CDKAL1 one of the most highly replicated genes identified.…”
Section: Discussionmentioning
confidence: 99%